2016
DOI: 10.5424/sjar/2016142-6848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhizobacteria on the respiration and growth of Cerasus sachalinensis Kom. seedlings

Abstract: In this study, we investigated the influence of rhizosphere microorganisms on seed germination and root metabolism in Cerasus sachalinensis Kom. We inoculated C. sachalinensis plants with suspensions of dominant bacterial strains isolated from their rhizosphere. Four bacterial strains each with significant growth-promoting or growth-inhibiting effects were screened from the efficient root-colonizing microorganisms. The number of actinomycetes increased and that of fungi decreased significantly in the seedling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Continuing our focus on symbiotic relations, bacteria may also influence root respiration rate by the release of some compounds to the rhizosphere ( Adesemoye and Egamberdieva, 2013 ). In this sense, some authors measured root respiration for bacterial inoculation, generally showing an increased root respiration rate ( Hadas and Okon, 1987 ; Phillips et al, 1999 ; Zhou et al, 2015 ; Qin et al, 2016 ). However, the effect of rhizobacterial bioaugmentation in roots has not been tested considering the electron partitioning between the COX and AOX pathways, much less under heavy metal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing our focus on symbiotic relations, bacteria may also influence root respiration rate by the release of some compounds to the rhizosphere ( Adesemoye and Egamberdieva, 2013 ). In this sense, some authors measured root respiration for bacterial inoculation, generally showing an increased root respiration rate ( Hadas and Okon, 1987 ; Phillips et al, 1999 ; Zhou et al, 2015 ; Qin et al, 2016 ). However, the effect of rhizobacterial bioaugmentation in roots has not been tested considering the electron partitioning between the COX and AOX pathways, much less under heavy metal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these results document the ability of Paenibacillus strain s37 to enhance the concentrations of both free and storage carbohydrates and affect their allocation in the different plant tissues. Other bacterial inoculants have been reported to increase affect plant carbohydrate levels ( Marcos et al, 2016 ; Qin et al, 2016 ) but the mechanism behind the effect of bacterial inoculations on the concentrations of plant carbohydrates is still poorly understood ( Magel et al, 2000 ; Gagné-Bourque et al, 2016 ). In consequence, there is a need to implement physiological phenotyping into a holistic phenomics approach ( Großkinsky et al, 2015 , 2018 ) to clarify how bacterial inoculation affects the regulation of carbohydrate metabolism in A. nordmanniana.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, stalk retention changes soil temperature, soil moisture, and soil nutrient status, especially in the tillage layer (Koiter and Lobb, 2008). Inversely, these soil property changes affect Rs (Isla et al, 2016;Qin et al, 2016). Diverse soil temperature experimental results have indicated that the Rs rate is closely related to soil temperature.…”
Section: Introductionmentioning
confidence: 99%